Establishment of Thripobius javae (semiluteus) in New Zealand - Jamieson, L.E.; Froud, K.; Edwards, R.; Stevens, P.S. (New Zealand Plant Protection, 2008)
The larval parasitoid Thripobius javae was imported from Italy into New Zealand in December 2000 as part of a classical biological control programme against greenhouse thrips (Heliothrips haemorrhoidalis) Thripobius javae was released from containment in Auckland in January 2001 Subsequent releases were made in 2001 at sites in Kerikeri Whangarei Bay of Plenty and Gisborne Release sites were monitored for greenhouse thrips and T javae 14 times between 2002 and 2007 Thripobius javae was recovered from 11 of the 21 release sites More intensive monitoring of a citrus orchard in Kerikeri found that 95100 of threetree plots had T javae present 1 year after release After 6 years the parasitoid was found in only 2128 of plots and had dispersed at least 200 m from this release site It has since been found in isolated areas where it was never released Using trap lemons infested with larval greenhouse thrips was not an effective method for detecting T javae Sticky traps did catch some parasitoids and may be a potential method for determining presence/absence